Mutants of Cochliobolus heterostrophus deficient in extracellular enzymes - Linda K. Lyngholm; Peggy R. Thorson; Caroline A. Spike; Charlotte R. Bronson (Fungal Genetics Reports, 1995)
Mutants with altered production and/or activity of certain extracellular enzymes have been obtained in Cochliobolus heterostrophus, a leaf spot pathogen of maize. The mutations should serve as useful phenotypic markers and can also be employed in studying the enzymes, their regulation, and their effect on other phenotypic traits, such as pathogenicity.